Tapered Implants in Dentistry: Revitalizing Concepts with Technology: A Review. (March 2016) - Wilson, T.G.; Miller, R.J.; Trushkowsky, R.; Dard, M.
The most common approach to lessen treatment times is by decreasing the healing period during which osseointegration is established. Implant design parameters such as implant surface, primary stability, thread configuration, body shape, and the type of bone have to be considered to obtain this objective. The relationship that exists between these components will define the initial stability of the implant. It is believed implant sites using a tapered design and surface modification can increase the primary stability in low-density bone. Furthermore, recent experimental preclinical work has shown the possibility of attaining primary stability of immediately loaded, tapered dental implants without compromising healing and rapid bone formation while minimizing the implant stability loss at compression sites. This may be of singular importance with immediate/early functional loading of single implants placed in poor-quality bone. The selection of an implant that will provide adequate stability in bone of poor quality is important. A tapered-screw implant design will provide adequate stability because it creates pressure on cortical bone in areas of reduced bone quality. Building on the success of traditional tapered implant therapy, newer tapered implant designs should aim to maximize the clinical outcome by implementing new technologies with adapted clinical workflows.